Analisis penerapan system application and product in data processing (SAP) pada sistem inventory logistik pada PT. Haier Sales Indonesia, Jakarta Utara - Ahmad Soleh; Resista Vikaliana (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
Rapid economic development causes increasingly fierce business competition. Moreover, the development of increasingly sophisticated technology, companies are competing to use technology to increase competitive advantage and efficiency in the company. One of the most popular information technology investments today is the Application of Systems and Products in Data Processing (SAP), systems that do business using a single database that can be accessed by all divisions within the company. The purpose of this research is to study and discuss the application of Systems and Products in Data Processing (SAP) conducted at PT. Haier Sales Indonesia. This study uses qualitative methods through in-depth interviews with IT Managers and Logistics Managers and warehouse administration staff using Pareto diagrams and fishbone diagrams. The results of the evaluation of the application of Application Systems and Products in Data Processing (SAP) in Inventory Logistics that occurred at PT. Haier Sales Indonesia is getting better, all data from every activity has been documented and integrated into the system much faster than the manual process that has been done before and can produce accurate reports. Suggestions are given in order to continue training in SAP Systems and Applications for users in developing SAP Systems and Applications.